Heat Release Rate Markers for the Adelaide Jet in Hot Coflow Flame - Ferrarotti, Marco; Amaduzzi, Ruggero; Bascherini, Davide; Galletti, Chiara; Parente, Alessandro (Frontiers in Mechanical Engineering, 2020)
In the present work, the correlation between the Heat Releaser Rate (HRR) and species mole fractions and net reaction rates is studied. The PaSR closure model is employed in a RANS framework to implement a detailed kinetic scheme, including the excited species OH*, used as a HRR marker. The effect of oxygen dilution on the combustion regime is investigated, as it can lead to Moderate or Intense Low-Oxygen Dilution (MILD) conditions. Two cases with different levels of oxygen concentration are analyzed. The results suggest the possibility of combining chemical species to construct an appropriate scalar to achieve better correlation with the HRR. It is found that typical markers such as radicals O, OH, OH* correlate fairly well with the HRR but improved correlations can be achieved with appropriate species mole fractions combinations, particularly for the MILD region of the flame.